2020
DOI: 10.1002/ptr.6986
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic compounds of Euphorbia umbellata (Pax) Bruyns (Euphorbiaceae) improved endothelial dysfunction through arginase inhibition

Abstract: Euphorbia umbellata is used for its anti-inflammatory properties; however, there are limited data available regarding its effects on vascular function. Its bark is rich in polyphenolic compounds, which potentially improve endothelial dysfunction (ED). This study proposes to investigate the effects of E. umbellata bark extracts and its polyphenolic compounds on arginase (ARG) activity and nitric oxide (NO)-related targets.Chromatographic procedures were used for the chemical characterisation of the extracts. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(73 reference statements)
1
0
0
Order By: Relevance
“…Only piceatannol-3′-O-β-D-glucopyranoside from rhubarb and polyphenolic compounds of Euphorbia umbellata have been reported to have a positive effect on ED by inhibiting Arg in STZ-induced diabetic mice and aged mice, respectively. 59,60 In our study, we confirmed that fenugreek extract, which contains flavonoids, saponins, and phospholipids, improves ED through the Arg1 pathway. This enriches the research on natural plant-based anti-Arg1 therapy for ED.…”
Section: Food and Function Papersupporting
confidence: 76%
“…Only piceatannol-3′-O-β-D-glucopyranoside from rhubarb and polyphenolic compounds of Euphorbia umbellata have been reported to have a positive effect on ED by inhibiting Arg in STZ-induced diabetic mice and aged mice, respectively. 59,60 In our study, we confirmed that fenugreek extract, which contains flavonoids, saponins, and phospholipids, improves ED through the Arg1 pathway. This enriches the research on natural plant-based anti-Arg1 therapy for ED.…”
Section: Food and Function Papersupporting
confidence: 76%